Exploring the potentials of sorghum genotypes: a comprehensive study on nutritional qualities, functional metabolites, and antioxidant capacities - Lee, Sukyeung; Choi, Yu-Mi; Shin, Myoung-Jae; Yoon, Hyemyeong; Wang, Xiaohan; Lee, Yoonjung; Yi, Jungyoon; Jeon, Young-ah; Desta, Kebede Taye (Frontiers in Nutrition, 2023)
Sorghum, long regarded as one of the most underutilized crops, has received attention in recent years. As a result, conducting multidisciplinary studies on the potential and health benefits of sorghum resources is vital if they are to be fully exploited. In this study, the nutritional contents, functional metabolites, and antioxidant capacities of 23 sorghum breeding lines and three popular cultivars were assessed. Total protein (9.05-14.61%), total fat (2.99-6.91%), crude fiber (0.71-2.62%), dietary fiber (6.72-16.27%), total phenolic (0.92-10.38 mg GAE/g), and total tannin (0.68-434.22 mg CE/g) contents varied significantly (p < 0.05). Antioxidant capacity, measured using three assays, also differed significantly. Palmitic, stearic, oleic, linoleic, and linolenic acids were detected using a gas chromatography-flame ionization detector and their contents varied significantly across the sorghum genotypes (p < 0.05). Moreover, liquid chromatography-tandem mass spectrometry analyses of 3-deoxyanthocyanidins and flavonoids detected luteolinidin, apigeninidin, 5methoxyluteolinidin, 7-methoxyapigeninidin, luteolin, and apigenin in the majority of genotypes at significantly different concentrations. Compared to the cultivars, some breeding lines had significantly high levels of metabolites and antioxidant activities. On the other hand, statistical analysis showed that total tannin, total phenolic, and antioxidant capacities varied significantly across white, yellow, and orange genotypes. Principal component analysis was used to differentiate the sorghum genotypes based on seed color and antioxidant index levels. Pearson's correlation analysis revealed strong links between biosynthetically related metabolites and those with synergistic antioxidant properties. In general, our research demonstrated the diversity of the sorghum resources investigated. Those genotypes with high levels of nutritional components, functional metabolites, and antioxidant activities could be used for consumption and breeding programs.